Micropropagation of Hedychium coronarium - C. Rungjindamai (2018)
The conventional seed propagation of H coronarium produced very few seedlings. This species has tendency to be endangered if appropriate propagation is not applied. Shoot buds of H. coronarium were cultured on MS semi-solid medium for shoot proliferation. The effects of plant growth regulators (PGRs), 2, 4 and 8 ppm 6-benzylaminopurine (BA) and 0.5, 1 and 2 ppm thidiazuron (TDZ) were investigated. The highest shoot proliferation of H. coronarium was 8.6±0.4 shoots per explant when cultured on MS semi-solid medium supplemented with 1 ppm TDZ for four weeks before subculturing to PGRs free MS medium for 12 weeks.